Handbook of Ugaritic studies - Watson, Wilfred G. E.; Wyatt, N. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 1999)
Over the past seven decades, the scores of publications on Ugarit in Northern Syria (15th to 11th centuries BCE) are so scattered that a good overall view of the subject is virtually impossible. Wilfred Watson and Nicolas Wyatt, the editors of the present Handbook in the series Handbook of Oriental Studies, have brought together and made accessible this accumulated knowledge on the archives from Ugarit, called 'the foremost literary discovery of the twentieth century' by Cyrus Gordon. In 16 chapters a careful selection of specialists in the field deal with all important aspects of Ugarit, such as the discovery and decipherment of a previously unknown script (alphabetic cuneiform) used to write both the local language (Ugaritic) and Hurrian and its grammar, vocabulary and style; documents in other languages (including Akkadian and Hittite), as well as the literature and letters, culture, economy, social life, religion, history and iconography of the ancient kingdom of Ugarit. A chapter on computer analysis of these documents concludes the work. This first such wide-ranging survey, which includes recent scholarship, an extensive up-to-date bibliography, illustrations and maps, will be of particular use to those studying the history, religion, cultures and languages of the ancient Near East, and also of the Bible and to all those interested in the background to Greek and Phoenician cultures.